Case report: Analysis of novel compound heterozygous TPP1 variants in a Chinese patient with neuronal ceroid lipofuscinosis type 2 - Miao, Sui-Bing; Guo, Hui; Kong, De-Xian; Zhao, Yuan-Yuan; Pan, Shu-Hong; Jiang, Yan; Gao, Xing; Wu, Xiao-Hua (Frontiers in Genetics, 2022)
Neuronal ceroid lipofuscinosis type 2 (CLN2) is an autosomal recessive neurodegenerative disease that is caused by variants in the TPP1 gene that lead to deficiency of the lysosomal enzyme tripeptidyl peptidase I (TPP1) activity. Here, we report a rare case of CLN2 caused by two novel variants of TPP1. The patient presented with seizures at onset,followed by progressive cognitive impairment, motor decline and vision loss. Novel compound heterozygous variants, c.544_545del and c.230-3C>G, in TPP1 were identified by whole-exome sequencing. Variant assessment showed that the c.544_545del is a frameshift variant mediating mRNA decay and that c.230-3C>G is a splice variant generating aberrantly spliced TPP1 mRNA, as confirmed by a Splicing Reporter Minigene assay. In conclusion, clinical history, variant assessment and molecular analyses demonstrate that the novel compound heterozygous variants are responsible for CLN2 disease in this patient. This study expands the mutation spectrum of TPP1.